Mainstreaming Multi, Inter, dan Transdisiplin Keilmuan dan Aktualisasinya pada Hadis Safar Perempuan - Nur Rohman; Thau’am Ma’rufah (KURAS Institute, 2024)
This article aimed to discuss the hadith of women travelling without a mahram with the Multi, Inter and Transdisciplinary way of thinking initiated by Amin Abdullah. This research is based on the fact that the monodisciplinary way of thinking, which has become a scientific problem, continues today. This way of thinking simultaneously gave birth to a textual way of looking at the text. One of the impacts is the understanding of the hadiths on women, which, if understood literally, often leads to certain restrictions on women. These restrictions, in turn, make it difficult for women to develop and be independent. Through a literature study, this article argues that the hadith about travelling for women has a moral meaning of safety as a condition whose purpose is to protect women. However, the studies on the hadith about travelling that some scholars have done have not explained what this security means. This article says that security is knowledge and other abilities that must be supplied and formed around women. In the context of migrant care, this perspective can be used as input for BP2MI to include religious elements and integrative ways of thinking in efforts to protect and solve the problems of Indonesian migrant workers in the future. This article is expected to contribute to the study of misogynistic hadith, the issue of migrant care and the actualization of a multidisciplinary perspective.